TRANSITIONS AMONG THE SECTIONS IN THE QURAN WORDING EXAMPLE OF NOAH’S PARABLE - İsmail BAYER (Fırat University, 2019)
The Quran presents its sections and messages that shed light from the history to the future in an impressive and eccentrical narrative fiction to the readers. Parables in Qur’an leades the reader’s imagination into the reality itself with a depiction of scene and life they impart to the dialogues. That the parables progress in the form of sections and stages rather than monolithic and take place dispersedly in the Quran is among its features. No connection can be identified with the traditional format and page-setting as we take for granted nowadays. The methods used in the connection and transition among sections are one of the most important parts of literary aspect of the parables. The connection among stages in the narration of the Quran parable occurs on general meaning, wordings and numbers. Wordings take place at related words and sound level (union or exchange of interruption). The matters that can express meaning in word and letter repetitions constitute an acceptance area depending on the controversial or personal preferences. Identifications of the connections in question makes the multi-dimentional integrity and astounding orderliness of Qur’an more appearant. On the other hand Qur’an makes its reader both intellectually and emotionally an active witness to the subject told in the text. The aim of our work is to investigate in the context of belief struggle enunciated in the Noah parable in Qur’an. composed of investigating the Quran once again in the context of transition among sections by centering the point of view of visual narrative type that has been dominant in the example of Noah parable nowadays.